Involvement of the tryptophan-kynurenine pathway in the pathogenesis of autoimmune diseases - A-Yuan Chen; Ying-Jie Zhao; Yue-Ye Wang; Wei Wei; Wei Hu; Yan Chang (Experimental Gerontology)
The kynurenine pathway (KP), a major metabolic pathway for L-tryptophan (Trp) in mammals, plays a multifaceted role in various physiological processes, including neural activity, immune system regulation, and the maintenance of intestinal homeostasis. The functional connection between the KP and immune system is supported by robust evidence, including disease-associated alterations in KP metabolite concentrations and enzyme activities that correlate with immune function changes. Imbalances in the KP can be detrimental, as excessive production of pro- or anti-inflammatory metabolites may promote autoimmunity or impair pathogen defense. To date, KP enzymes and metabolites have been extensively studied as both promoters and therapeutic targets in a wide array of autoimmune diseases (AID). Pharmacological modulation of the KP represents a promising therapeutic strategy, as it can regulate immune responses and attenuate disease progression in AID. However, the precise cellular and molecular mechanisms by which the KP contributes to AID pathogenesis remain incompletely understood. This review explores the complex mechanisms through which KP enzymes and metabolites regulate inflammatory immune responses in AID, and highlights potential therapeutic targets for drug development.